Determinants Determinants of Firm Value in LQ45 Companies Listed on the Indonesia Stock Exchange - Lulu Ayu Afriyani; Siti Nurlaela; Suhendro Suhendro (Politeknik Ganesha Medan, 2026)
This study aims to analyse the effect of profitability, liabilities, dividend policy, capital structure, and asset turnover on firm value in companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX) for the period 2021–2024. Firm value is measured using the Price to Book Value (PBV) ratio, while the independent variables consist of Return on Assets (ROA), Debt to Asset Ratio (DAR), Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO). This study employs a quantitative approach using secondary data derived from the financial statements of LQ45 companies. Sample selection was conducted through purposive sampling, resulting in 19 companies with a total of 72 observations after excluding 4 outlier data. Data were analysed using multiple linear regression with SPSS version 25, complemented by classical assumption tests, F-test, t-test, and coefficient of determination. The results of the t-test indicate that profitability, liabilities, and asset turnover have a significant effect on firm value, whereas dividend policy and capital structure do not have a significant effect. Furthermore, the F-test results demonstrate that profitability, liabilities, dividend policy, capital structure, and asset turnover simultaneously have a significant effect on firm value. These findings provide empirical evidence that firm value in LQ45 companies is primarily driven by profitability, efficient asset utilisation, and optimal liability management, and are expected to serve as a reference for investors and management in formulating strategies to enhance firm value.